Beneficial Effects of Polysaccharides on the Epithelial Barrier Function in Intestinal Mucositis - Sauruk da Silva, Karien; Carla da Silveira, Bruna; Bueno, Laryssa Regis; Malaquias da Silva, Liziane Cristine; da Silva Fonseca, Lauany; Fernandes, Elizabeth Soares; Maria-Ferreira, Daniele (Frontiers in Physiology, 2021)
Intestinal mucositis is a clinically relevant side effect of anticancer therapies. It is experienced by 60–100% of patients undergoing treatment with high doses of chemotherapy, radiation therapy, and bone marrow transplantation. Intestinal mucositis can manifest as pain, weight loss, inflammation, diarrhea, rectal bleeding, and infection; affecting normal nutritional intake and intestinal function. It often impacts adherence to anticancer therapy as it frequently limits patient’s ability to tolerate treatment, causing schedule delays, interruptions, or premature discontinuation. In some cases, local and systemic secondary infections are observed, increasing the costs toward medical care and hospitalization. Several strategies for managing mucositis are available which do not always halt this condition. In this context, new therapeutic strategies are under investigation to prevent or treat intestinal mucositis. Polysaccharides from natural resources have recently become promising molecules against intestinal damage due to their ability to promote mucosal healing and their anti-inflammatory actions. These effects are associated with the protection of intestinal mucosa and regulation of microbiota and immune system. This review aims to discuss the recent advances of polysaccharides from natural resources as potential therapies for intestinal mucositis. The source, species, doses, treatment schedules, and mechanisms of action of polysaccharides will be discussed in detail.